2012
DOI: 10.1123/jsr.21.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Respiratory-Muscle Exercise on Spinal Curvature

Abstract: The spinal curvature was significantly different in the Ex group, indicating a decrease in the thoracic (-13.1%, P < .01) and lumbar (-17.7%, P < .05) angles. The Ex group presented with lower thoracic (-8.6%) and lumbar (-20.9%) angles at postexercise than the Cont group (P < .05). With respect to trunk-muscle strength, only trunk-flexion strength significantly increased from pretest to posttest in the Ex group (P < .05). For pulmonary function, forced vital capacity and forced expiratory volume in 1.0 s were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 31 publications
4
29
0
1
Order By: Relevance
“…There exist very few reports of prospective studies that evaluated the effects of specific exercises on spinal alignment (26)(27)(28)(29)56). In one study, it was found that spinal extension exercises could delay the progression of kyphosis angle (26).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There exist very few reports of prospective studies that evaluated the effects of specific exercises on spinal alignment (26)(27)(28)(29)56). In one study, it was found that spinal extension exercises could delay the progression of kyphosis angle (26).…”
Section: Discussionmentioning
confidence: 99%
“…Kuo et al (27) found that a Pilatesbased exercise program reduced the thoracic curve in healthy older adults, whereas Greendale et al (28) reported that yoga decreased kyphosis in senior women and men with adult-onset hyperkyphosis. Another study showed that respiratory-muscle exercises decreased thoracic curve and straightened the spine, leading to good posture control (29). Park et al (57) investigated the effects of prone trunk extension exercises in their slouched thoracic posture group in comparison to the control group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The spine of the growing athlete is more vulnerable; prolonged excessive strains may contribute to changes in the shape of AP curvatures of the spine, which in turn, result in the development of low back pain [18,25,26,28,29]. Such changes may also result in back, chest or abdominal muscle tension closely related to postural imbalance and might decrease the flexibility of the shoulder girdle [30][31][32].…”
Section: Introductionmentioning
confidence: 99%